2021
DOI: 10.2147/dhps.s337791
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Compliance and Associated Quality of Amoxicillin in Drug Retail Outlets of Southwestern Ethiopia

Abstract: Background: While the research findings confirm the existence of private drug retail outlets that do not comply with regulatory standards in many low-income countries, there are a lack of reports that evaluate the quality of medicines obtained from these firms. Therefore, the aim of this study was to evaluate the regulatory compliance of the retails and associated quality of amoxicillin in Southwestern Ethiopia. Methodology: Forty-two drug retail outlets in Jimma town were evaluated using an inspection checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A recent review of the current literature found that the antibiotic failure frequency (the proportion of samples in a prevalence study that failed at least one quality test) was 15.7% for private pharmacies 31 . In a demonstrated combined sampling and testing study included in this review, the assays of amoxicillin obtained from non‐compliant retail outlets appeared to be slightly degraded compared to compliant retail outlets, although still within pharmacopoeial limits 12 . Additionally, in another study included in this review in which the microbiological potency of sampled antibiotics were tested, pharmacy air conditioning was significantly associated with potency 15 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A recent review of the current literature found that the antibiotic failure frequency (the proportion of samples in a prevalence study that failed at least one quality test) was 15.7% for private pharmacies 31 . In a demonstrated combined sampling and testing study included in this review, the assays of amoxicillin obtained from non‐compliant retail outlets appeared to be slightly degraded compared to compliant retail outlets, although still within pharmacopoeial limits 12 . Additionally, in another study included in this review in which the microbiological potency of sampled antibiotics were tested, pharmacy air conditioning was significantly associated with potency 15 .…”
Section: Discussionmentioning
confidence: 84%
“…Full study characteristics are provided in Table 1, and further details are provided within the quality assessment in Table S1. Of the 15 studies, publication dates ranged from 2007 to 2021, with the majority published in 2021 ( n = 6) 12,14–16,23,26 , and 10 countries were represented by those 15 studies, with the majority located in Asia and Africa. Five studies investigated outlets in Pakistan 17,21,23–25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations